PRAGMATIC ARCHITECTURE IN SETIABUDI VERTICAL HOUSING DESIGN IN SOUTH JAKARTA, BASED ON URBAN FARMING - Aldi Ryan; Karya Widyawati; Fery Mulya Pratama (Lakar: Jurnal Arsitektur, 2023)
DKI Jakarta is the province with the most populous population in Indonesia with apopulation of 10.64 million people and has increased by 0.38% since 2021 according to DKI Jakarta census data in 2021. With such a large population it is a frightening specter for Jakarta coupled with the depletion of land for Building settlements makes the issue of limited land even more apprehensive. For this reason, it is necessary to create solutions to overcome the limited residential land in Jakarta and put forward the social and environmental context. Vertical housing is one of the solutions emphasized by the DKI Jakarta government to overcome the issue of limited land in Jakarta. Apart from that, economic and social values are also growing along with the development of vertical housing development using the concept or basis of urban farming in order to maintain food security in DKI Jakarta.